How much is too much? (Part 1) International Olympic Committee consensus statement on load in sport and risk of injury. Issue 17 (17th August 2016) - Soligard, Torbjørn; Schwellnus, Martin; Alonso, Juan-Manuel; Bahr, Roald; Clarsen, Ben; Dijkstra, H Paul; Gabbett, Tim; Gleeson, Michael; Hägglund, Martin; Hutchinson, Mark R; Janse van Rensburg, Christa; Khan, Karim M; et al.
Abstract : Athletes participating in elite sports are exposed to high training loads and increasingly saturated competition calendars. Emerging evidence indicates that poor load management is a major risk factor for injury. The International Olympic Committee convened an expert group to review the scientific evidence for the relationship of load (defined broadly to include rapid changes in training and competition load, competition calendar congestion, psychological load and travel) and health outcomes in sport. We summarise the results linking load to risk of injury in athletes, and provide athletes, coaches and support staff with practical guidelines to manage load in sport. This consensus statement includes guidelines for (1) prescription of training and competition load, as well as for (2) monitoring of training, competition and psychological load, athlete well-being and injury. In the process, we identified research priorities.